PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA SMA NEGERI 3 MERANGIN - Joko Sutanto; Ade Susanti; Muhammad Jainuri (Hiradika | Hira Institute, 2025)
Low mathematics scores of students caused by the lack of students' ability to solve problems in the real world is a problem that must be solved by applying the RME approach. The main objective of this study is to improve mathematics learning outcomes. This study uses the PTK method, which was carried out for two cycles, in SMA Negeri 3 Merangin Class X C, with 33 students. The PTK method has four stages of activity: (1) planning (2) implementation (3) observation and (4) reflection. The results of the study showed that in cycle I, the average score obtained was 73.88, with an average completion of 73% (24 students) and an average student learning activity reaching 74%. While in cycle II, the average score increased to 81.06, with an average completion of 85% (28 students) and student learning activities reaching 83%. From the explanation, it can be seen that learning outcomes increased by 12% from cycle I to cycle II, while student learning activities increased by 9%. Thus, the implementation of the Realistic Mathematics Education (RME) approach can improve the learning outcomes of class X C students of SMA Negeri 3 Merangin in the 2024/2025 Academic Year.